3D research challenges in cultural heritage. III, Complexity and quality in digitisation - Ioannides, Marinos; Patias, Petros; Ohio Library and Information Network (Cham : Springer, 2023)
This open access book presents a collection of papers focusing on current 3D research challenges in the domain of cultural heritage. 3D technologies find considerable use within the field of cultural heritage, for example in the areas of data acquisition, modeling, archiving in local repositories, and harvesting in digital libraries. This volume focuses on a number of challenges facing 3D research in the field of cultural heritage, including the digitization of objects and their transformation to digital/virtual twins; the interplay of geometry and semantics for cultural heritage; the organization of large 3D databases in cultural heritage; the handling of 3D data via the Internet and mobile devices; the presentation of cultural heritage content in 3D to the general public; and the reconstruction of cultural heritage objects from virtual to real and their 3D production and use.
The Complexity and Quality in 3D Digitisation of the Past: Challenges and Risks Towards sustainable digitization -- Technology solutions for complex and challenging survey projects -- Evolving Standards in Digital Cultural Heritage - Developing a IIIF 3D Technical Specification -- The Quality in 3D Acquisition of Cultural Heritage Assets: Challenges and Risks -- How to measure Quality Models? Digitization into Informative Models Re-Use -- The Holistic Documentation of movable cultural heritage objects - the case of the Antikythera Mechanism -- "Digital Documentation of Reflective Objects: A cross-polarised photogrammetry workflow for complex materials"
Includes author index.
Keywords: Cultural property -- Computer simulation; Three-dimensional imaging in archaeology; Electronic books